Novel Alanyl-tRNA Synthetase 2 Pathogenic Variants in Leukodystrophies - Wang, Xingao; Wang, Qun; Tang, Hefei; Chen, Bin; Dong, Xiang; Niu, Songtao; Li, Shaowu; Shi, Yuzhi; Shan, Wei; Zhang, Zaiqiang (Frontiers in Neurology, 2019)
The white matter disease spectrum is associated with many genetic diseases, including AARS2, CADASIL, ALD, and others. In this study, to determine the novel alanyl-tRNA synthetase 2 mutation implicated in white matter disease, several families with an autosomal recessive inheritance pattern of white matter disease were analyzed by whole-exome sequencing. Variants were prioritized according to their rarity and pathogenic variants in genes already known to be associated with leukodystrophies and were confirmed by Sanger sequencing using standard protocols. We identified 5 rare variants (c.452T>C chr6:44279256 p.M151T, c.1871G>A chr6:44272054 p.W624X, c.802A>G chr6:44278128 p.M268V, c.1703-1704del chr6:-44272430-44272431 p.Q568fs, and c.179C>A chr6-44280882 p.P60H) with varying expression in 4 independent Chinese families with leukodystrophy. These single nucleotide variants (SNVs), or deletion mutations, each induced a frameshift, causing a missense mutation in alanyl-tRNA synthetase 2. These findings suggested that all mutations might contribute to the development of leukodystrophy in the examined family members. Combined with previous findings, our data confirmed that the novel mutations are located in leukodystrophy-related risk genes. We also summarized all the alanyl-tRNA synthetase 2 mutations related to the onset of leukodystrophies in adults.